What behavioral interventions are effective for pediatric habit cough?. Issue 7 (July 2015) - Bryant, Matthew E.; Syed, Shima
Abstract : Evidence‐Based Answer : Self‐hypnosis, biofeedback, and suggestion may be effective treatments for pediatric habit cough (SOR: C, small case series and case reports).